Os efeitos do microcrédito na renda dos beneficiários: Análise do Programa Crescer - Napole\~ao Luiz Costa da Silva; Alice Saccaro; Jéssica Faciroli (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The Programa Crescer is a sub-program under the Programa Nacional de Microcredito Produtivo Orientado (PNMPO), considered a microcredit policy aimed at low-income formal and informal micro-entrepreneurs, providing credit without collateral and with interest rates subsidized by the Governo Federal, in force from 2011 to 2014. Under the agenda of granting small amounts of credit to unassisted entrepreneurs and small production units, this study aims to verify the effect and economic viability of the Grow Program on the incomes of beneficiaries, using information from the Cadastro Único para Programas Sociais do Governo Federal (Cadastro Único) between the periods 2010 to 2019. The Propensity Score Matching with Differences - Differences and cost-benefit analysis methods were used to achieve the objectives. The results showed that after the Programa Crescer came into force, the effect on individuals' incomes varied from 6.37% in 2015 to 5.42% in 2019, about the economic return, for the subset of individuals belonging to Cadastro Único, it was positive and high, concluding that the benefits in terms of raising individuals' incomes were higher than the costs in terms of interest subsidies on loans.
Keywords: H8; C01; I3; 330; Crescer Program; microcredit; micro-entrepreneurs; formal; informal; income